PURIFICATION AND CHARACTERIZATION OF POLYSACCHARIDE FROM MICROALGAE BTM 11 AS INHIBITOR OF HEPATITIS C VIRUS RNA HELICASE - Apon Zaenal Mustopa; Aksar Chair Lages; Muhammad Ridwan; Linda Sukmarini; Dwi Susilaningsih; Hasim; Delicia (Universitas Gadjah Mada, 2015)
Hepatitis C virus is one of the causative agents for HCV-related liver disease development with high virulence. Antiviral drugs can be discovered through molecular target-based therapy by finding the inhibitors for RNA helicase that play crucial role in viral replication. An inhibitor can be derived from polysaccharides produced by microalgae. In this study, polysaccharide from microalgae BTM11 which had inhibitory activity against RNA helicase have been purified and characterized.On the other hand, the RNA helicase was produced by E. coli BL21(DE3)pLyss harboring NS3 RNA helicase HCV gene in pET-21b plasmid. This enzyme then was purified by affinity chromatography and this purified enzyme was used for HCV RNA helicase inhibitory assay. Polysaccharide fractions were separated from the extract of BTM 11 using Sepharose 4B column chromatography. Inhibitor activity was measured using colorimetry ATPase assay based on releasing of phosphate inorganic. The results of SDS-PAGE and Western blot showed that the purified RNA helicase had a molecular weight of 54kDa. The highest inhibition activity of HCV RNA helicase (88 ± 2,4726%) was achieved at fraction 10 of purified polysaccharide. The HPLC result showed that compounds of polysaccharide active fraction were maltopentose (Rt 4.183) and glucose (Rt 5.673). Both of 1H-NMR and IR spectra showed hydroxyl and carbonyl groups that present in the polysaccharide structure.